Systematic review of ecosystem services flow measurement: Main concepts, methods, applications and future directions - Wang, Lijuan; Zheng, Hua; Chen, Yongzhe; Ouyang, Zhiyun; Hu, Xiaofei (Ecosystem services, 2022)
•We reviewed concepts, methods and applications of studies which have measured ecosystem services flow (ESF).•There were multiple definitions of ESF resulting in multiple measurement methods.•ESF is widely used to measure nature’s contribution to people and understand the nature–human relationship.•Ecological process-based dynamic flow models should be used to measure ecosystem services flow in the future. Studying the whole process of ecosystem services (ES) realization by people (ecosystem services flow) is the key to ES management. However, varying concepts of relative ecosystem services flow (ESF) and different methods for measuring ESF have prevented its effective application in policy and management. In addition, there has been no systematic review of the concepts, methods and application of ESF. To address this research gap, we conducted a systematic review of ESF measurement, focusing on the main concepts, methods and applications. We used the key words ““ecosystem service*” AND (“flow*” OR “delivery*”)” in the core collection of the ISI Web of Science databases, with the aim of synthesizing the concepts, methods and applications of ESF. We propose future research directions to move the field of ESF toward a more accepted and consistent set of terminology and scientific practice. Eighty-two case studies were eventually selected for the review. We found that different understandings of the definition of ESF (actual use amount as flow, spatial connection as flow, flow process as flow and other flow) resulted in different measurement methods. Measuring the whole process of ESF may help us measure nature’s contribution to people, understand the relationship between supply and demand, which will facilitate the development of regional planning and policies (e.g. spatial conservation planning, infrastructure planning, interregional management), and in turn increase ESF. To effectively apply ESF in the future, first, we recommend combining existing flow definitions and redefining ESF as the whole ESF realization process with more focus on human needs. Second, ecological process-based dynamic models should be developed or improved to assess ESF by integrating the beneficiaries. Third, we should consider the impacts of both natural and human-derived capital on the delivery of ESF and ways to strengthen interregional flow management. Overall, this article contributes to a more comprehensive understanding of the definition, methods and application for measuring ESF, which in turn will inform ES policy implementation.